The Practice of Skilled Nurses in the Care of Patients Diabetes Mellitus: Scoping Review - Suriadi, Suriadi; Dewi, Eka Ratna (CV. Publikasi Indonesia, 2025)
Diabetes mellitus (DM) is a chronic disease with rising global prevalence, posing significant morbidity and mortality challenges. Skilled nurses play a pivotal role in DM management through holistic care, yet disparities in nursing knowledge, self-management practices, and resource limitations hinder optimal outcomes. This scoping review aims to map proficient nursing practices in DM care, identify barriers to effective self-management, and evaluate the impact of nurse-led interventions on patient outcomes. A systematic search was conducted on PubMed, Scopus, and Google Scholar (2015–2025) using keywords like